ln(x+3)+ln(x-3)=4

Simple and best practice solution for ln(x+3)+ln(x-3)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+3)+ln(x-3)=4 equation:


Simplifying
ln(x + 3) + ln(x + -3) = 4

Reorder the terms:
ln(3 + x) + ln(x + -3) = 4
(3 * ln + x * ln) + ln(x + -3) = 4
(3ln + lnx) + ln(x + -3) = 4

Reorder the terms:
3ln + lnx + ln(-3 + x) = 4
3ln + lnx + (-3 * ln + x * ln) = 4
3ln + lnx + (-3ln + lnx) = 4

Reorder the terms:
3ln + -3ln + lnx + lnx = 4

Combine like terms: 3ln + -3ln = 0
0 + lnx + lnx = 4
lnx + lnx = 4

Combine like terms: lnx + lnx = 2lnx
2lnx = 4

Solving
2lnx = 4

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '2nx'.
l = 2n-1x-1

Simplifying
l = 2n-1x-1

See similar equations:

| 3x+5y+2x+3x+5x+7-4= | | -4x+-12x-39=137 | | 1.3(x+3)+2.3x=6 | | 6p-1=3p+8 | | x(4+x)= | | -4x+-12-39=137 | | 4x^2-10x+3= | | -2p+7=5-1(7p+2) | | 2(x+2)+x=7 | | (12.4)(14)(t)=1042 | | 12x^4y-4x^3y^2= | | -2p+8=6-(11p+3) | | 1+t=-4 | | -(4u-7v+w)= | | 8=24+r | | 12x^4y*-4x^3y^2= | | 3t^2-13t+10=0 | | 7w+18=0 | | -9=n-18 | | 3x+x^2-1=4x^2-4 | | 6(x-1)=36 | | -23=p-1 | | 3a-7a-12=32 | | -0.9x-3.4=1.1 | | 11x+20=12x+2 | | y(y+9)= | | 12x-4=4x+28 | | (3.14)(2)(y)=12.56 | | 2=8+4 | | 6.6(x-3)=-0.4x+22.2 | | -24-.125p=.357p | | 8(4s-3)+4-32s= |

Equations solver categories